Combined Learning (face-to-face/virtual) and the Development of Written Communication Skills - Solano Córdoba, Olga Ligia (2013)
This paper summarizes the results of the research project El aprendizaje combinado (presencial y no presencial apoyado por el uso de internet)  y su utilidad para el desarrollo de las habilidades de expresión escrita [The Use of Combined Learning (face-to-face and virtual) in Developing Written Expression Skills] conducted in 2011-2012 with the support of the Office of the Vice-President for Research of the Costa Rica Institute of Technology. This research-action study was focused on exploring and systematizing the contribution of combined learning activities (bimodal courses) to develop written expression skills. Didactic strategies were designed to use forums, wikis, blogs, bibliography managers, concept mapping software, as well as online spelling checkers and dictionaries as means to promote the use of written language in relevant contexts. The total study population included eighty-one students from the University of Costa Rica and the Costa Rica Institute of Technology, and thirteen faculty members (ten were higher education teachers, three were teachers of the Ministry of Public Education of Costa Rica working with students from the 7th to the 11th grades, and there was a teacher working in both contexts). The outcomes of the project were evaluated through the analysis of products selected, panel discussions with the participant teachers, interviews to the participant population, and the analysis of the researcher’s project journals.  This study concludes that combined learning contributes to improving written expression skills, since it involves the development of skills and competencies to accomplish different tasks related to the access of knowledge on a specific topic to be developed in writing, text planning, text production, proofreading and dissemination of the final product.